MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA HURUF MAGNETIK BAGI ANAK BERKESULITAN BELAJAR MEMBACA - Retno Sulistyowati (Jurnal Penelitian Pendidikan Khusus, 2014)
ABSTRACT This research was background by the problems of researcher found in school that a is learning disabilities child in second class in the SDN 09 Pauh Padang hoving. Troubles getting summation of the reading beginning is reading the words on the consonant cluster [ng] in the beginning, in the middle, at the end, and double consonants [ny] at the beginning, and in the middle. Under these conditions, this research purpose to prove letters of magnetic media in improving the ability in reading beginning for learning disabilities child second class in the SDN 09 Pauh Padang.   Kata Kunci: Anak Kesulitan Belajar Membaca; Membaca Permulaan; Media Huruf Magnetik.